Perbedaan Pengetahuan Gizi Tentang Anemia dan Angka Kesakitan Antara Siswi Anemia dan Non Anemia di SMK Penerbangan Bina Dhirgantara Karanganyar - Haryanti, Santi; , Dwi Sarbini, S.ST., M.Kes; , Ahmad Farudin, SKM,M.Si (2016)
Introduction: The prevalence of anemia at Bina Dhirgantara Flight Vocational High School Karanganyar is high, which was 56.8%. Anemia is a condition in which the hemoglobin level is less than the normal value. One of causes of anemia is the lack of knowledge in the community about anemia. Anemia which is often the case in the community is iron deficiency anemia, which the iron sufficiency greatly affect the immune response to fight infection. Objective: This study aimed to determine the differences of nutrition knowledge of anemia and morbidity between anemia and non anemia female students at Bina Dhirgantara Flight Vocational High School Karanganyar. Methods: The study was observational with cross sectional approach. Subjects were obtained through total sampling method, which were 43 subjects. Data of hemoglobin used cyanmethemoglobin method. Data of nutritional knowledge about anemia and morbidity rate were obtained by using a questionnaire in 43 subjects. Data were analyzed using Independent t-test. Results: Based on research subjects of 43 students consistins of 23 female students anemia and 20 students non anemia. It was obtained that 75% of students had poor knowledge about the nutritional anemia, while students which were categorised as often get sick were 66.7%. The percentage of female students who were non-anemia and had good nutritional knowledge about anemia was 66,7%, while students which were categorised never get sick were 87.5%. Statistical test results showed that there were differences of nutritional knowledge about anemia between anemia and non anemia female students, and there was differences in morbidity between anemia and non anemia female students. Conclusions: There were differences of nutritional knowledge and morbidity between anemia and non anemia of female students at Bina Dhirgantara Flight Vocational High School Karanganyar.